Desarrollo de una aplicación móvil con administración web para promocionar y gestionar el flujo de ventas del servicio de guíanza turística que ofrece la compañía de turismo “Boliche Tours”. - Paredes Vargas, Cristian Marcelo (2021)
This technological proposal was made in the province of Cotopaxi in the city of Latacunga, where it was identified in the tourism company Boliche Tours, disseminates information through flyers and people who recommend their services, the management of customer reservations is done manually, which causes loss of information and inconsistency in the reservations, for this reason the objective of the technological proposal is to develop a mobile application with web administration to promote and manage the flow of sales of tourist guide service using free software tools such as: Laravel, PHP, MySQL, Java and Android Studio. For the proposed study has been defined the research: Quantitative, Qualitative and NonExperimental Design, using techniques and instruments such as observation, interview and survey, in order to understand the problem and identify why the inadequate strategies of promotion and sales management of the tourist guide service offered by the Boliche Tours Company attract few customers. In the development of the web application the XP methodology was used and for the mobile environment Mobile-D was used using the different phases for its development, obtaining as a result the systematization in the process of promotion and management of reservations of tourist packages reaching more people, it is concluded that with the implementation of the web and mobile application will provide timely information, optimizing processes and increasing the satisfaction of customers and partners of the company. It is recommended to use the XP methodology because it allows to respond with confidence to their changing requirements.